2009
DOI: 10.3164/jcbn.08-255
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Low Serum Paraoxonase-1 in Subjects with Coronary Artery Disease

Abstract: Paraoxonase-1 (PON-1), an HDL-associated enzyme has been shown to possess antioxidant/anti-inflammatory properties and protect against atherogenesis. The aim of the study was to explore the association of PON-1, with lipids, antioxidant-vitamins and lifestyle in male subjects with and without angiographically documented coronary artery disease (CAD) and in healthy volunteers. PON-1 activity was measured spectrophotometrically using phenyl acetate as substrate. PON-1 and HDL-Cholesterol were significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 24 publications
(28 reference statements)
4
39
1
Order By: Relevance
“…In the current study, PON1, ghrelin and AE activity were found to be significantly lower (p<0.05) in workers occupationally exposed to cement dust than in the control groups. This could be related to enhanced lipid peroxidation, (9) since oxidized lipids are reported to inhibit PON1 activity (34,35). Decreased PON1 and AE blood serum levels observed in the cement dust exposed subjects could also have been caused by a change in HDL secondary levels or decreased protein expression as a result of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, PON1, ghrelin and AE activity were found to be significantly lower (p<0.05) in workers occupationally exposed to cement dust than in the control groups. This could be related to enhanced lipid peroxidation, (9) since oxidized lipids are reported to inhibit PON1 activity (34,35). Decreased PON1 and AE blood serum levels observed in the cement dust exposed subjects could also have been caused by a change in HDL secondary levels or decreased protein expression as a result of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…PON1, an antioxidant enzyme, circulates in the blood and is associated with HDL particle, and can destroy lipids in the form of oxidised low-density lipoproteins (Sahin et al 2004). Jayakumari and Gopalan (2009) observed that low serum PON1 activity is correlated with low serum vitamin C, suggesting that PON1 level is positively correlated with the anti-oxidant level. Jarvik et al (2002) reported that vitamin C is a positive predictor of PON1, and its level increases with anti-oxidant vitamins.…”
Section: Discussionmentioning
confidence: 80%
“…There is not enough clinical data to support this concept of functional deficiency in HDL as a contributing factor for the increased prevalence of CHD. Earlier study from this laboratory revealed that serum levels of HDL-C and paraoxonase-1, an antioxidant enzyme associated with HDL, showed inverse association with the presence of CHD but were not related to the severity of disease in terms of number of diseased vessels [14].It is not clear that measuring plasma concentrations of HDL-C are sufficient to capture the functional variations in HDL particles along with the associated cardiovascular risk. Therefore, it is highly essential to evaluate functional characteristics of HDL, such as antioxidant and antiinflammatory functions as well as HDL-associated biomarkers that better predict cardiovascular risk.…”
Section: Introductionmentioning
confidence: 97%